Towards optimizing the operation of microbial electrolysis cells for heavy metal removal - Fuller, Erin (My University, 2018)
Heavy metals are a growing environmental concern as they are unable to be metabolized in the environment, leading to bioaccumulation in the food chain and impacting human health. Treating heavy metals is difficult and expensive. Current methods include precipitation (which generates sludge that is costly to dispose of) or requires the use of a membrane, which fouls and requires regeneration. Microbial electrolysis cells (MECs) represent an alternative for treating heavy metal contaminated wastewater. Reactor components are cheap, and operation requires only a small amount of electricity. The electrically active biofilm oxidizes organics in the wastewater while transferring electrons first to the anode, then to the cathode, where aqueous metals are reduced to a solid deposit, a mechanism called electrodeposition. Few studies have been conducted to investigate the best operational conditions for heavy metal removal in MECs. In this study, the effects of hydrodynamics, applied voltage, and initial metal concentration on heavy metal removal mechanisms are investigated, and the best operational practices are determined on a high level. Mixing in the cathode chamber increased electrodeposition by 15%, decreased the cathode potential by -0.06 V, and increased current generation between 10-30%. Increasing the applied voltage from 0.6 V to 1.2 V increased electrodeposition by 22%. With both mixing and higher voltage applied, 93.35% of cadmium was removed from the catholyte in 24 hours. Although high voltage application maximized electrodeposition for short-term treatment, long-term treatment indicated lower applied voltage resulted in healthier MEC reactors, better overall metal recoveries, along with a more stable cathode potential.
Keywords: microbial electrolysis cells; bioelectrochemical system; heavy metal removal; wastewater